TPACK Leadership Diagnostic Tool: Adoption and Implementation by Teacher Education Leaders. Issue 1 (2nd January 2019) - Clausen, Jon M.; Finsness, Elizabeth S.; Borthwick, Arlene C.; Graziano, Kevin J.; Carpenter, Jeffery P.; Herring, Mary
Abstract: This case study describes how leaders from three teacher education institutions utilized a technological, pedagogical, and content knowledge (TPACK) leadership diagnostic tool in the design, development, and implementation of technology rich initiatives. Participants were interviewed to find out how the diagnostic tool guided their decision making. Content analysis and a priori coding were used to analyze transcripts along with constant comparative methods to explore elements within the diagnostic tool and identify additional codes. Results indicate that education leaders utilized the TPACK leadership diagnostic tool in different ways to guide the design, development, and implementation of their technology initiatives. Participants also provided recommendations for how the diagnostic tool and its use might be enhanced in order to support change.